2002
DOI: 10.1007/s00444-002-0348-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluoreszenz-in-situ-Hybridisierung (FISH) an nichtkultivierten Amnionzellen zur Diagnostik häufiger Chromosomenstörungen

Abstract: Abb.1a-f Zellkerne nichtkultivierter Fruchtwasserzellen mit chromosomenspezifischen Hybridisierungssignalen. Normales Signalmuster des (a) CEP-Sondenmixes und (b) LSI-Sondenmixes bei einem männlichen Feten. Fruchtwasserzellen mit 3 Fluoreszenzsignalen: (c) Trisomie 13, (d) Trisomie 18 und (e) Trisomie 21. (f) Triploidie dargestellt mit dem CEP-Sondenmix

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…ABBOTT.com). Röpke et al (2002) confirmed these data by literature review. In seven publications (Eiben et al, 1999a;Bink et al, 2000;Pergament et al, 2000;Thein et al, 2000;Ulmer et al, 2000;Tepperberg et al, 2001;Weremowicz et al, 2001) describing 13,763 FISH analyses using the AneuVysion assay, only three false-positive (0.02%) and ten false-negative (0.07%) cases were reported.…”
supporting
confidence: 77%
“…ABBOTT.com). Röpke et al (2002) confirmed these data by literature review. In seven publications (Eiben et al, 1999a;Bink et al, 2000;Pergament et al, 2000;Thein et al, 2000;Ulmer et al, 2000;Tepperberg et al, 2001;Weremowicz et al, 2001) describing 13,763 FISH analyses using the AneuVysion assay, only three false-positive (0.02%) and ten false-negative (0.07%) cases were reported.…”
supporting
confidence: 77%